Marketing Strategies in Increasing Skill Interest in Rida Embroidery Ponorogo Course and Training Institutions - Nurrantika Aini; Reni Mulazamah; Siti Suliyah; Tias Fajar Widowati; Tita Seviana; Tunjung Genarsih (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
Marketing strategy is a centralized and comprehensive plan to achieve business goals through a marketing mix that includes product, pricing, location, and promotional strategies. The purpose of this study is to find out how LKP Rida Embroidery's marketing strategy in increasing public interest in attending courses and training. The research method used is field research with descriptive qualitative data analysis. Research shows that LKP Rida Embroidery uses a promotional strategy by conducting training in making deliveries and offerings, in addition to collaborating with schools. In addition, promotion uses social media such as Instagram, Facebook and direct promotion.